Irony and Drama : a Poetics - States, Bert O. (Cornell University Press, 2019)
Professor States provides nothing less than a new theory of the drama based upon the principles of irony and dialectic. Very close in approach to the Continental structuralists, he treats irony, not as a literary device or as an attitude in the mind of the playgoer, but as a means of confronting reality-a way of testing and resolving conflicting ideas. Pointing out the limitations of conventional categories such as comedy, tragedy, and tragicomedy, he views drama instead as a vehicle for perceiving and ordering the possibilities of human experience. After setting forth his thesis boldly and persuasively, Professor States explores other mod es such as the epic and the lyric and shows how they interact with the dramatic principle. He manages to cover, in a minimum amount of space, the entire range of dramatic styles and periods, placing special emphasis on playwrights of universal appeal like Sophocles, Shakespeare, Chekhov, Ibsen, Shaw, and Beckett.